NIEGHBOURHOOD WATCH: A VEHICLE FOR COMBATING CRIME IN PORT HARCOURT URBAN OF RIVERS STATE, NIGERIA - Ferdinard Okpo, Justice; Orji, Benneth (PT. Antis International Publisher, 2025)
Objective: This study examines the effectiveness of Neighborhood Watch schemes as a strategy for combating crime in Port Harcourt Urban, Rivers State, Nigeria, with the aim of enhancing National security through community participation. Method: A qualitative approach was adopted, involving in-depth interviews and focus group discussions with community members, local leaders, and security personnel to explore their perceptions and experiences with Neighborhood Watch initiatives. Results: The findings reveal that the indifferent attitude of residents toward crime prevention undermines government efforts in ensuring public safety. However, active community involvement through Neighborhood Watch programs significantly enhances crime control by fostering collaboration between citizens and security agencies. Novelty: This study highlights the role of communal responsibility in crime prevention, providing new insights into how grassroots participation can be leveraged to strengthen National security frameworks. It offers a paradigm shift from conventional state-centric security models to a more inclusive approach, emphasizing the importance of civic engagement in crime management.